Bio-based innovation: Assessing the suitability of Solanum nigrum stem fibers for textile and biomedical applications - Ganesan Subbiah; Manjunath Channappagoudra; Deepak Bhanot; Vijay J. Upadhye; Sasanka Choudhury; Krishna Kumar Shukla; Kamakshi Priya Kumar (Results in Engineering)
The growing demand for sustainable alternatives in textile and biomedical industries has spurred interest in natural fibers. This study aimed to evaluate the potential of Solanum nigrum stem fibers as a renewable material through comprehensive physicochemical and biological characterization. Raw fibers were extracted via water retting and subjected to a series of analyses. Structural properties were examined using X-ray diffraction and Fourier Transform Infrared spectroscopy, while thermal stability was assessed through thermogravimetric analysis. Morphological features were investigated using scanning electron microscopy, and mechanical performance was evaluated through tensile testing. Biological activity was analyzed using antibacterial assays and biofilm inhibition studies. The fibers showed moderate crystallinity (78.43 %), good thermal resistance up to 320 °C, and a fibrous morphology favourable for composite applications. Mechanical tests revealed a tensile strength of 9.53 MPa and Young’s modulus of 6.41 GPa. Antibacterial tests against Escherichia coli exhibited a 13 mm inhibition zone, with 72.6 % biofilm reduction, highlighting the fiber's potential for antimicrobial use. Overall, the results suggest that Solanum nigrum fibers are a viable, eco-friendly option for developing sustainable textile products and biomedical materials.